An Updated Checklist and Perspective Study of Millipedes (Arthropoda: Myriapoda: Diplopoda) in the Korean Peninsula - Anh D. Nguyen (Animal Systematics, Evolution and Diversity, 2016)
The Korean peninsula has diverse habitats and so would be expected to have a rich millipede fauna because of its location between the Paleoarctic and Oriental regions. To facilitate studies on millipedes, this work provides an updated list and discussion of Korean millipedes. A total of 69 species had been recorded up to 2010, but since then no new species have been reported. Among 69 species, 49 are endemic to the Korean peninsula. From 1950 to the present, an average of only seven new species from the Korean peninsula has been described per decade. This number does not reflect the biodiversity of millipedes in Korea, especially when compared to Taiwan, which has only one-third the area of the Korean peninsula, but from which a greater number of millipede species have been recorded (75 vs. 69 species). Japan has twofold the land area of the Korean peninsula, and an almost threefold higher number of millipede species. Further, more-intensive surveys will likely result in identification of more millipede species in the Korean peninsula.